The Role of Corpus Linguistics in Contemporary Linguistics Research and Translation Studies - Pei, Haitong (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 2, I͡A︡zykoznanie., 2025)
The article presents a systematic review of research papers on corpus linguistics as an innovative direction in empirical linguistics. It reveals the theoretical and methodological foundations of the field, defines the specifics of corpus linguistics in comparison with computational linguistics, and highlights modern trends in corpus research as well as the advantages of employing textual corpus data in linguistic studies. It is noted that the corpus method and its resources are actively used in various linguistic researches into many world languages today; that language corpora are differentiated by volume, type, structure, content, purpose, etc. The article provides an overview of such corpora as the British National Corpus (BNC), the American National Corpus (ANC), the Corpus of Contemporary American English (COCA), the Russian National Corpus (RNC), and the Modern Chinese Language Corpus created in the Center for Chinese Linguistics at Beijing University, the Balanced Corpus of the Chinese Language. The specifics of parallel and comparative corpora are noted, including the Child Language Data Exchange System (CHILDES), the International Comparable Corpus (ICC), and the Corpus of English Wikipedia (CEW). The differences between parallel and comparative corpora are also outlined. Prospects for national corpora development lie in new research into almost every area of applied and theoretical linguistics, as well as in scrutiny and further development of translation theory and practice. The characteristics of monolingual, comparative, and parallel corpora are highlighted in the context of their role in linguistic research. It is mentioned that, in addition to parallel corpora, translators' tools also include monolingual corpora, which provide additional material on the subject of translation and enhance the translator's background knowledge.